Management of patients with HIV-1 infection by pharmacist prescribers: an evaluation of practice. Issue 1 (23rd July 2013) - Nicholls, Jane S; Butt, Mandeep; Ogden, David; Snelling, Mel; Weston, Rosy
Abstract : Objectives: This paper describes the self-evaluation and peer review of the practice of a group of self-selected pharmacist prescribers managing patients with HIV-1 infection in secondary care settings in the UK. Methods: Pharmacist prescribers who were responsible for managing an episode of care for adult HIV patients within defined clinical settings were invited to participate. The project lead worked with the volunteers to define, pilot and use a data collection tool for prospective data collection. Results: Four pharmacist prescribers agreed to participate and a tool was developed and used for prospective data collection over 6 months for a total of 95 patient consultations. The pharmacists were providing a number of different models of service delivery as either scheduled or unscheduled appointments, face-to-face or on the telephone. The primary purpose of the consultations ranged from initiation and optimisation of therapy to maintenance of supply of medicines and adherence advice. An attempt was made to look at patient outcomes in terms of viral load, and prescribing error rate was 1.2% of prescribed items. Conclusions: This evaluation suggests that pharmacist prescribers are able to safely and effectively manage episodes of care for patients with HIV-1 infection. Use of the data collection tool was found to be relatively simple and could be used for routine self-assessment or further study. Limitations include the small size and the self-assessment by practitioners. Further work should focus on an evaluation of the service against the BHIVA Standards 2013 and the patient experience.